Browning control in coconut palms tissue culture - de Siqueira, Edemar Ramos; Inoue, Mario Takao (Pesquisa Agropecuaria Brasileira, 1991)
The purpose of this study was to develop technology in order to avoid browning in tissue culture of coconut (Cocos nucifera L.) tree. In the antioxidant treatments citric and ascorbic acids were used for explants of young plant leaves, and polyvinylpyrrolidone (P VP for explants of adult leaves and inflorescence. Citric and ascorbic acids control 50% of browning incidence. The initial culture in liquid media was increasingly efficient in the control of this process, resulting in high rates of healthy explants obtention.